The cost of dying : [large type] the violent days of Lou Prophet, bounty hunter - Brandvold, Peter (Brandvold, Peter. Bounty hunter Lou Prophet series., 2020)
"Of all the legends of the Old West, few are as stained with ink, blood, and bullets as the violent days of bounty hunter Lou Prophet. But what happens when the hunter becomes the hunted? Heaven knows there'll be hell to pay . . . THE DEVIL RIDES AGAIN After a hard night with his sometime lover Louisa Bonaventure--"the Vengeance Queen"--Lou Prophet decides to cool his heels at a local honky tonk. Things heat up fast when he defends one of the girls from a sadistic brute who also happens to be the deputy sheriff. And now Prophet is running for his life . . . WITH A BOUNTY ON HIS HEAD Heading south of the border to Mexico, Prophet isn't the only man marked for death. The young red-headed pistolero Colter Farrow has made an awful lot of enemies, too--and now practically every bounter hunter south of the Rio Grande is gunning for blood. For money. For fun. And, now, for Lou Prophet . . "--